Effects of microbial inoculation on composting of household organic waste using passive aeration bin - Somjai Karnchanawong (2018)
© 2014, The Author(s). Background: The effects of microbial inoculation with two commercial inoculants and mature compost on the composting of household organic wastes were investigated using five 200-L passive aeration compost bins. Food scraps and dry leaves (1.6 kg total) with a ratio of 1:0.14 (wet weight) were added to each bin once a day, for 60 days, and then further composted for an additional 94 days. The temperature in each bin was recorded daily. Weekly to biweekly, a composite sample of the compost from each bin was analyzed. Results: The C/N ratios of composts in the un-seeded and seeded bins stabilized at 81 days and 67–74 days, respectively. The highest volatile solid mass reduction was achieved in the bin seeded with 5 % mature compost. Conclusions: The study revealed that it might not be necessary to add commercial inoculants to facilitate composting of household organic waste. Mature compost can be used as a seed starter to improve composting.